Relationship of Family Support to Medication Compliance in Pulmonary Tuberculosis Patients - Tuti Yanuarti (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Tuberculosis (TB) is a disease caused by infection with Mycobacterium Tuberculosis. According to World Health Organization (WHO) figures, there were 10.4 million instances of tuberculosis events in 2016 (8.8 million-12 million), which is comparable to 120 cases per 100,000 population. India, Indonesia, China, the Philippines, and Pakistan have the highest incidence of instances. Health Status According to the Ministry of Health of the Republic of Indonesia, West Java province had the highest number of TB infections in Indonesia in 2016, with 52,328 cases. Methods: This study's design is descriptive analytic using a cross-sectional approach. In the TB DOTS poly space, 71 patients with pulmonary tuberculosis were sampled. Purposive sampling procedures are used to obtain samples. Primary data collected directly from respondents / informants through a questionnaire are used in research data collection methodologies.Univariate and bivariate (Chi-square) analyses were utilized, with a significance limit of Alpa = 0.05. Results: According to the findings of this study, there is a strong association between family support and medication adherence in patients with pulmonary tuberculosis (P = 0.000). Conclusion: In the DOTS Polyclinic Hospital, there is a relationship between family support and medication adherence among the three factors.